2018
DOI: 10.1017/jfm.2017.879
|View full text |Cite
|
Sign up to set email alerts
|

Forced synchronization of periodic and aperiodic thermoacoustic oscillations: lock-in, bifurcations and open-loop control

Abstract: Synchronization is a universal concept in nonlinear science but has received little attention in thermoacoustics. In this numerical study, we take a dynamical systems approach to investigating the influence of harmonic acoustic forcing on three different types of self-excited thermoacoustic oscillations: periodic, quasi-periodic and chaotic. When the periodic system is forced, we find that: (i) at low forcing amplitudes, it responds at both the forcing frequency and the natural (self-excited) frequency, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 56 publications
4
41
0
Order By: Relevance
“…Such a type of suppression phenomenon was experimentally evidenced in the control of ion-sound instability (Keen & Fletcher 1969), in self-excited ionization waves (Ohe & Takeda 1974) and even in the control of thermoacoustic instability (Guan et al 2018). Further, the reduction in response amplitude of thermoacoustic oscillation forced at non-resonant frequencies has been reported in previous studies (Lubarsky et al 2003;Bellows et al 2008;Guan et al 2018;Kashinath et al 2018). However, they did not focus on explaining the mechanism behind such a quenching of natural oscillations due to forcing.…”
Section: Forced Synchronization and Amplitude Quenchingmentioning
confidence: 96%
See 1 more Smart Citation
“…Such a type of suppression phenomenon was experimentally evidenced in the control of ion-sound instability (Keen & Fletcher 1969), in self-excited ionization waves (Ohe & Takeda 1974) and even in the control of thermoacoustic instability (Guan et al 2018). Further, the reduction in response amplitude of thermoacoustic oscillation forced at non-resonant frequencies has been reported in previous studies (Lubarsky et al 2003;Bellows et al 2008;Guan et al 2018;Kashinath et al 2018). However, they did not focus on explaining the mechanism behind such a quenching of natural oscillations due to forcing.…”
Section: Forced Synchronization and Amplitude Quenchingmentioning
confidence: 96%
“…Further, characterizing the dynamical states and mechanisms of amplitude reduction in the context of dynamical systems theory is essential for a better understanding of the phenomenon. In a recent study by Kashinath, Li & Juniper (2018), forced synchronization leading to periodic, quasiperiodic and chaotic states is investigated quite elaborately using a simple model of a ducted laminar flame; however, experimental realization of this study is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In thermoacoustics, open-loop forcing has been shown to be able to weaken periodic self-excited oscillations in various combustion systems, ranging from the simple Rijke tube (Reynolds numbers of Re ∼ 10 3 with natural frequencies of f 1 ∼ 10 2 Hz; Guan, Murugesan & Li 2018;Kashinath et al 2018;Guan et al 2019a;Mondal, Pawar & Sujith 2019) to turbulent premixed combustors (Re ∼ 10 4 , f 1 ∼ 10 2 Hz; Bellows, Hreiz & Lieuwen 2008;Balusamy et al 2015). A recurring theme of these studies has been the application of periodic acoustic forcing to periodic thermoacoustic oscillations, accompanied by an examination of the nonlinear dynamics en route to and beyond the synchronization boundaries.…”
Section: Forced Synchronization Of Periodic Oscillationsmentioning
confidence: 99%
“…Forced synchronization of quasiperiodic thermoacoustic oscillations 393 From a control perspective, numerous studies have shown that, near the onset of synchronization, the thermoacoustic amplitude can be drastically reduced -typically to less than 20 % of that of the unforced state (Bellows et al 2008;Kashinath et al 2018;Guan et al 2019a,b;Mondal et al 2019). This reduction occurs via asynchronous quenching, a nonlinear process in which the amplitude of a self-excited oscillator is reduced by the external application of periodic forcing at a frequency far enough from the natural frequency to prevent resonant amplification of the forcing signal (Minorsky 1967).…”
Section: Forced Synchronization Of Periodic Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation